Depression and Cardiovascular Healthcare Costs among Women with Suspected Myocardial Ischemia: Prospective Results from the Women’s Ischemia Syndrome Evaluation (WISE) - Rutledge, Thomas (2009)
OBJECTIVES: We evaluated three novel questions in a prospective clinical cohort of women undergoing evaluation for suspected myocardial ischemia (1) What is the relationship between depression and cardiovascular costs; (2) Does the relationship vary by definition of depression?; (3) Do depression-costs relationship patterns differ among women with versus without coronary artery disease (CAD)? BACKGROUND: Comorbid depression has been linked to higher medical costs in previous studies of cardiovascular patients. METHOD: 868 women presenting with suspected myocardial ischemia completed an extensive baseline examination including cardiovascular risk factor assessment and coronary angiogram. Depression was defined by: 1) current use of antidepressants; 2) a reported history of depression treatment; and 3) Beck Depression Inventory scores. Direct (hospitalizations, office visits, procedures, and medications) and indirect (out-of-pocket, lost productivity, and travel) costs were collected through 5-years of follow-up to estimate cardiovascular costs. RESULTS: A range of 17–45% of women was depressed using the above study criteria. Depressed women showed adjusted annual cardiovascular costs $1,550–$3,300 higher than non-depressed groups (r’s=.08–.12, p’s<.05). Depression-costs relationships also varied by coronary artery disease status, with stronger associations present among women without evidence of significant CAD. CONCLUSIONS: Depression was associated with 15–53% increases in 5-year cardiovascular costs, and cost differences were present using three definitions of depression. The results reinforce the importance of assessing depression in clinical populations and support the hypothesis that improved management of depression in women with suspected myocardial ischemia could reduce medical costs.